Nursing residency and sense of coherence: Motivations and coping strategies for facing challenges (Research, Society and Development, 2026)
Objective: To describe the relationship between the Sense of Coherence and the motivations and strategies used by a nursing resident to cope with challenges experienced during in-service training.Method: An experience report developed within the Clinical and Surgical Nursing Residency Program of the municipal healthcare network of Rio de Janeiro, Brazil. Data were produced through reflective notes recorded throughout the first year of residency, in the medical clinic and surgical center sectors, and organized into thematic axes based on the Salutogenesis Theory. Results: Four thematic axes emerged: training process; motivations for entering the program; challenges related to quality of life; and significant moments. The Sense of Coherence was found to favor resilience, focus, and emotional reorganization.Conclusion: The Sense of Coherence is a powerful framework for understanding the daily experiences of nursing residents and may support institutional strategies aimed at promoting mental health and strengthening the training process.